Selection Quiz Competition Participants With the Profile Matching Method (Case Study: Kesuma Bangsa Middle School , Padang Lawas) - Fuji Handayani Fuji Handayani (Journal of Information System and Artificial Intelligence, 2025)
A quiz contest is a contest of intelligence and brevity in answering questions involving mathematics, civics, social science, Indonesian, and others. The candidates for this competition are carefully chosen based on the aspects and criteria held by the organization. This selection process aims to discern candidates who can accurately and efficiently answer the questions given. A reliable method to spot the merited candidates is highly necessary for the procedure. Due to that background, this research aspires to develop a decision support system by the Profile Matching method. Profile Matching method consists of three aspects: intelligence, attitude, target, and nine criteria: knowledge, commitment, innovation, diligence, teamwork, discipline, honesty, focus, and creativity. On the test result report of systemic count and current situation with 20 participants, there were 16 participants whose data were qualified (80%) and 4 participants whose data were not.